Reframing teacher vocation through ethics: Deontological foundations for educational practice - Castillo-Lamadrid, Jorge Luis (Edelweiss Applied Science and Technology, 2025)
The teaching profession faces increasing ethical and vocational challenges in a globalized and technocratic educational context. In Latin America, particularly in Peru, the weakening of professional commitment and the undervaluation of ethical responsibility have generated growing concerns about the integrity and purpose of teacher education. This study addresses this issue by analyzing how professional vocation and deontological principles shape educational practice, identity, and policy. The objective of this research is to examine the relationship between teacher vocation and professional ethics from a deontological perspective and to assess how these elements contribute to the quality and integrity of teaching in the Peruvian educational system. A systematic review was conducted using the PRISMA protocol, analyzing 23 peer-reviewed articles indexed in Scopus, Scielo, and Web of Science from 2020 to 2024. The selection criteria focused on studies addressing ethics, teacher identity, vocation, and educational governance. The analysis revealed four emergent thematic categories: (1) the erosion of vocational identity in neoliberal systems, (2) the role of ethical frameworks in shaping teacher performance, (3) vocation as a dynamic construct developed through experience, and (4) deontology as a normative foundation for pedagogical action. Despite institutional codes of ethics, ethical education remains insufficiently integrated into teacher training in Peru. The study concludes that teacher vocation, grounded in deontological ethics, is essential for sustaining educational quality, professional responsibility, and social trust. Its findings offer actionable insights for educational governance, curriculum design, and teacher policy in developing contexts.